Tree and cold storage influence on incidence of albedo breakdown, textural properties of the rind and fruit quality in 'Washington Navel' orange - Ahmad, S.; Singh, Zora; Iqbal, Z. (Elsevier, 2016)
Introduction. Albedo breakdown (AB) causes serious economic losses to sweet orange growers. The growers practice delayed harvesting (tree storage) to extend the fresh fruit supply to market. We investigated the effects of tree storage and cold storage on AB incidence, textural properties of the rind and fruit quality. Materials and methods. Fruit of ‘Washington Navel’ orange were harvested at the commercial maturity stage (3rd July) and then 31, 62 and 93 days after the harvest. The AB incidence, textural properties of the rind and fruit quality were assessed in one lot of fruit after harvest and a second lot after 31, 62 and 93 days of cold storage (5 °C). Results and discussion. The AB incidence increased from 65% to 89% from the first to the last harvest, respectively. Extended storage periods reduced rind hardness and fruit firmness, and increased the rind tensile force irrespective of the storage type. The rind hardness, tensile force and fruit firmness were higher in cold-stored fruit than fruit stored for 93 days on the tree. The soluble solids concentration: titratable acidity (SSC:TA) ratio in juice increased with the extended storage period in both types of storage. The increase in SSC:TA was more pronounced at 62 and 93 days in cold-stored than tree-stored fruit. The concentrations of fructose and glucose in the juice of fruit stored on the tree for 93 days were higher than in the cold-stored fruit, and sucrose showed the reverse trend. Conclusion. The cold-stored fruit exhibited a higher rind hardness, rind tensile force, firmness and SCC:TA ratio, lower concentrations of citric acid, malic acid, fructose and glucose, and lower AB incidence than the tree-stored fruit. These findings indicate a preference for cold storage over tree storage for the orange fruit quality.